The effects of extender egg yolk concentration, penetrating cryoprotectant (amide only vs. amide + glycerol), and pre-freeze cooling rate on post-thaw quality of stallion sperm - V. Zhidkov; L. Ramirez-Agamez; J. Crowley; J.C. Samper; C.C. Love; C. Hernandez-Aviles (Journal of Equine Veterinary Science, 2025)

Global sensitivity analysis of reactive transport modelling for the geochemical evolution of a high-level radioactive waste repository - J. Samper; C. López-Vázquez; B. Pisani; A. Mon; A.C. Samper-Pilar; F.J. Samper-Pilar (Applied Geochemistry, 2025)

Benchmarking of reactive transport codes for 2D simulations with mineral dissolution–precipitation reactions and feedback on transport parameters - J. Poonoosamy; C. Wanner; P. Alt Epping; J. F. Águila; J. Samper; L. Montenegro; M. Xie; D. Su; K. U. Mayer; U. Mäder; L. R. Van Loon; G. Kosakowski (Computational Geosciences, 2021)

Toward a Coordinated Global Observing System for Seagrasses and Marine Macroalgae - J. Emmett Duffy; Lisandro Benedetti-Cecchi; Joaquin Trinanes; Frank E. Muller-Karger; Rohani Ambo-Rappe; Christoffer Boström; Alejandro H. Buschmann; Jarrett Byrnes; Robert G. Coles; Joel Creed; Leanne C. Cullen-Unsworth; Guillermo Diaz-Pulido; et al. (Frontiers in Marine Science, 2019)

Freedom from Tritrichomonas foetus infection in cattle in St. Kitts - Kimberly E. Coker; Joseph J. Lim; Rebecca L. Schleisman; Christopher Vosloo; Hilari M. French; Juan C. Samper; John J. Callanan; Robert O. Gilbert; Fortune Sithole; Chaoqun Yao; Aspinas Chapwanya (Tropical Animal Health and Production, 2018)

Anticipative management for coral reef ecosystem services in the 21st century - Alice Rogers; Alastair R. Harborne; Christopher J. Brown; Yves‐Marie Bozec; Carolina Castro; Iliana Chollett; Karlo Hock; Cheryl A. Knowland; Alyssa Marshell; Juan C. Ortiz; Tries Razak; George Roff; et al. (Global Change Biology, 2015)
Under projections of global climate change and other stressors, significant changes in the ecology, structure and function of coral reefs are predicted. Current management strategies tend to look to the past to set goals, focusing on halting declines and restoring baseline conditions. Here, we explore a complementary approach to decision making that is based on the anticipation of future changes in ecosystem state, function and services. Reviewing the existing literature and utilizing a scenario planning approach, we explore how the structure of coral reef communities might change in the future in response to global climate change and overfishing. We incorporate uncertainties in our predictions by considering heterogeneity in reef types in relation to structural complexity and primary productivity. We examine 14 ecosystem services provided by reefs, and rate their sensitivity to a range of future scenarios and management options. Our predictions suggest that the efficacy of management is highly dependent on biophysical characteristics and reef state. Reserves are currently widely used and are predicted to remain effective for reefs with high structural complexity. However, when complexity is lost, maximizing service provision requires a broader portfolio of management approaches, including the provision of artificial complexity, coral restoration, fish aggregation devices and herbivore management. Increased use of such management tools will require capacity building and technique refinement and we therefore conclude that diversification of our management toolbox should be considered urgently to prepare for the challenges of managing reefs into the 21st century.

Comparative assessment of climate change and its impacts on three coastal aquifers in the Mediterranean - T. Y. Stigter; J. P. Nunes; B. Pisani; Y. Fakir; R. Hugman; Y. Li; S. Tomé; L. Ribeiro; J. Samper; R. Oliveira; J. P. Monteiro; A. Silva; et al. (Regional Environmental Change, 2014)

Evaluation of alternative nitrogen and carbon sources for sugarbeet suspension culture platings in development of cell selection schemes - J. W. Saunders; C. J. Tsai; E. Samper (In Vitro Cellular & Developmental Biology - Plant, 1997)